The Impact of Functional Asymmetry of the Cerebral Hemispheres in Students of a Physics and Mathematics Lyceum on the Learning Outcomes - Ikkert, Oksana; Korol, Tetiana; Hlazunova, Kateryna; Tsinkevych, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2025)
The functional asymmetry of the human brain hemispheres (motor, sensory, and mental) reflects the differences in the distribution of neuro-psychic functions between the left and right hemispheres. The left hemisphere is responsible for the brain's abstract-logical, inductive thinking, and verbal-analytical functions. The right hemisphere provides visual-figurative, deductive thinking. The dominance of the left hemisphere determines left-hemispheric thinking, while the dominance of the right hemisphere determines right-hemispheric thinking. The synchronous functioning of both hemispheres indicates balanced-hemispheric thinking. According to this distribution, different styles and effectiveness of students' cognitive activities will be observed. Therefore, our goal was to investigate and compare the types of cerebral hemisphere dominance in students of a physics and mathematics lyceum studying in classes with physics-mathematics and chemistry-biology specializations. We found that 84.4% of students of both genders, regardless of their chosen specialization, had left-hemisphere dominance with an average level of functional asymmetry. Among students of the chemistry-biology specialization who actively participate in Olympiads, there are representatives with left hemispheric (high, medium, and low asymmetry coefficients), right hemispheric, and balanced-hemispheric functional organization of the brain. Among students of the physics-mathematics specialization involved in Olympiads, there were children with left-hemispheric thinking (low and medium asymmetry coefficients). Among 14 students who participated in Olympiads, 86% (12) were right-handed, and 14% (2) were left-handed. This indicates that the type of interhemispheric asymmetry is not a factor that causes learning difficulties or vice versa. The article summarizes the necessity of considering the individual psychophysiological characteristics of students in the educational process, particularly their functional asymmetry of the cerebral hemispheres. It emphasizes the need to implement appropriate forms, methods, and teaching techniques in lessons that align with specific types of thinking to activate the potential of both cerebral hemispheres in students of a physics and mathematics lyceum with mathematical and biological specializations.